Revelation : from metaphor to analogy - Swinburne, Richard (Oxford : Clarendon Press ; New York : Oxford University Press, 2007)
"This is a fuller and entirely rewritten second edition of Revelation, the most notable new feature of which is a long chapter examining whether traditional Christian claims about personal morality (divorce, homosexuality, abortion etc.) can be regarded as revealed truths. A formal appendix shows how the structure of evidence supporting the Christian revelation can be articulated in terms of the probability calculus (and shows that Plantinga's well known argument from 'dwindling probabilities' against probabilistic arguments of this kind is not cogent)."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Revelation -- Christianity; Metaphor -- Religious aspects -- Christianity; Analogy (Religion)